EFL Learners’ Attitudes towards the Use of the Cooperative Learning Method in Learning Speaking - Chioukh, Chadia; Kaouache, Salah (Journal of Human Sciences, 2021)
The aim of the present paper is to probe the EFL learners’ perceptions of learning the speaking skill within the scope of the Cooperative Learning (CL) method. Moreover, the study pursues to illuminate the classroom practices embraced by the teachers and learners of English as a foreign language to develop speaking and considers the compatibility of these practices with the Cooperative Learning basic tenets. To attain the set goals, a questionnaire has been designed and administered to 69 first year (licence) English Language university learners at Mohammed Seddik Ben Yahia University-Jijel. The findings revealed the learners’ inclination to espouse CL while learning the speaking skill albeit they did not sufficiently apply all its five elements. In addition, teachers’ practices were not fittingly aligned with the CL method principles.